The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1145/2983621
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Locally Injective Mappings

Abstract: InitializationIteration 20 Iteration 40Figure 1: A locally injective, energy minimizing parameterization of a mesh with over 25 million triangles computed with our algorithm in 80 minutes. The algorithm starts from a highly distorted locally injective initialization and in only 40 iterations, each requiring to solve a sparse linear system, it converges to a highly isometric map that is guaranteed to be free of inverted elements. AbstractWe present a scalable approach for the optimization of flippreventing ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 50 publications
(3 reference statements)
2
79
0
Order By: Relevance
“…This paper contributes several new ideas to parameterization and related optimization problems in geometry. We stress that our method matches or exceeds the performance of existing methods [KGL16, RPPSH17] while enjoying additional theoretical understanding and a remarkably simple matrix construction. Specific contributions include the following:…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…This paper contributes several new ideas to parameterization and related optimization problems in geometry. We stress that our method matches or exceeds the performance of existing methods [KGL16, RPPSH17] while enjoying additional theoretical understanding and a remarkably simple matrix construction. Specific contributions include the following:…”
Section: Introductionmentioning
confidence: 59%
“…In this paper, we take inspiration from recent preconditioners that accelerate first‐order (gradient‐based) optimization for mesh parameterization [SS15, KGL16, RPPSH17]. We formulate a new preconditioner specifically designed for parameterization problems, using the language of vector field design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the preconditioner will fail to give good results if the stability term of the functional Fh becomes dominant.On the other hand, the numerical experience in these situations is that the mesh is already nearly deteriorated if the stability term becomes dominant, which usually only happens if, for example, the boundary deformation is about to produce self‐intersections at the boundary. This indicates problems in whatever is governing the boundary deformation; thus, the arising ill‐conditioning of the mesh optimisation problem is usually the least of all worries. The quadratic proxy distortion measures in the work of Rabinovich et al are quite similar to a preconditioner.…”
Section: Methodsmentioning
confidence: 99%
“…For velocity‐based methods, successful approaches for generating orientation preserving mesh deformations have been for the purpose of using an attraction/repulsion model for vertices, for geometric conservation law‐based, or for directly specifying the determinant of the deformation gradient, but without being able to control the cell shapes . Examples for location‐based methods are using the (parabolic) Monge‐Ampère equation or the biharmonic equation or modelling the mesh as a hyperelastic material; see also the work of Rabinovich et al for surface mesh parametrisation using similar deformation energies and that of Persson and Peraire for a hyperelasticity‐based approach to higher‐order mesh generation. An in‐depth literature review can be found in the work of Budd et al Generally speaking, most mesh optimisation methods do not enforce the orientation preserving property directly (see the work of Shontz and Vavasis for a combination of a linear method and a postprocessing step) or even identify it as the major culprit, as they are more concerned with optimising the cell size distribution in a very regular domain.…”
Section: Introductionmentioning
confidence: 99%